1996
DOI: 10.1128/jvi.70.1.383-392.1996
|View full text |Cite
|
Sign up to set email alerts
|

Four of eleven loci required for transient complementation of human cytomegalovirus DNA replication cooperate to activate expression of replication genes

Abstract: As previously shown, 11 loci are required to complement human cytomegalovirus (HCMV) DNA replication in a transient-transfection assay (G. S. Pari and D. G. Anders, J. Virol. 67:6979-6988, 1993). Six of these loci encode known or candidate replication fork proteins, as judged by sequence and biochemical similarities to herpes simplex virus homologs of known function; three encode known immediate early regulatory proteins (UL36-38, IRS1/TRS1, and the major immediate early region spanning UL122-123); and two enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 63 publications
(104 reference statements)
4
57
0
Order By: Relevance
“…or create a local environment suitable for efficient synthesis of viral DNA replication proteins in the naturally permissive HF cells. Note that they also failed to associate any transactivation function with UL84 expression, consistent with our interpretation that its role in replication is potentially direct (42). Thus, the requirement for such transactivators in DNA replication can most likely be explained by a dependence on cooperative regulatory interactions of multiple loci for the efficient expression of cellular and viral replication proteins.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…or create a local environment suitable for efficient synthesis of viral DNA replication proteins in the naturally permissive HF cells. Note that they also failed to associate any transactivation function with UL84 expression, consistent with our interpretation that its role in replication is potentially direct (42). Thus, the requirement for such transactivators in DNA replication can most likely be explained by a dependence on cooperative regulatory interactions of multiple loci for the efficient expression of cellular and viral replication proteins.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the removal of UL112-113 from the replication assay severely reduced the detectable level of oriLyt amplification. Recently, Iskenderian et al (42) argued that the cooperative interactions observed between some of the auxiliary factors are critical to either produce a synergistic enhancement of HCMV early promoters 7408 SARISKY AND HAYWARD J. VIROL. or create a local environment suitable for efficient synthesis of viral DNA replication proteins in the naturally permissive HF cells.…”
Section: Discussionmentioning
confidence: 99%
“…The HCMV UL84 is a nonstructural early protein which has been shown to interact with the HCMV immediate-early protein IE86 (23,66). UL84 is also required in the complementation assay for replication of a plasmid containing the HCMV origin of replication (25,48). Interestingly, the 6.9-kb transcript, which likely encodes the M84 product, is detectable only at 8 h p.i., consistent with early gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The HCMV UL36-38 locus is required for its oriLyt DNA replication [101][102][103][104]. Expression of nuclear genes, including induction of the human heat shock protein 70 (hsp70) and selected HCMV early genes, can be regulated by pUL37x1\vMIA and gpUL37 [78,105,106].…”
Section: Transactivationmentioning
confidence: 99%